Relative susceptibility of banana cultivars to Xanthomonas campestris pv. musacearum - Tripathi, L.; Tripathi, J.N. (2009)
The banana Xanthomonas wilt (BXW) is the most devastating disease of banana in Great Lakes region of East and Central Africa. The pathogen kills plants quickly and spreads rapidly over a large area in a short time making the disease one of the most dreaded in banana. The disease affects almost all varieties of commonly grown banana cultivars. Some knowledge of the relative susceptibility of banana cultivars would be extremely useful and could be a basis for management strategies for BXW. Ten banana cultivars were evaluated for their relative susceptibility to Xanthomonas campestris pv. musacearum. All the ten cultivars were tested by injecting bacterial inoculum in pseudostem of in vitro plantlets as well as potted plants. The various banana cultivars showed significant differences in susceptibility to Xanthomonas campestris pv. musacearum. The beer banana cultivar ‘Pisang Awak’ and dessert cultivars ‘Dwarf Cavendish’, ‘Giant Cavendish’, and ‘FHIA-17’ were found to be highly susceptible, whereas East African Highland banana cultivar ‘Nakitembe’ was found to be least susceptible. The other cultivars ‘Mpologoma’, ‘Mbwazirume’, ‘Sukali Ndiizi’ and ‘FHIA-25’, were found to be susceptible. Diploid parent ‘Musa balbisiana’ was found to be resistant. This study clearly highlights the need for development of new resistant cultivars for BXW disease control, as all the commercial cultivars are susceptible.